The Different Bio-Effects of Functionalized Multi-Walled Carbon Nanotubes on tetrahymena pyriformis - Guo, Jinxue; Zhang, Xiao; Zhang, Shusheng; Zhu, Ying; Li, Wenxin (Current Nanoscience, 2008)
To promote the applications of namomaterials, the potential toxicity of multi-walled carbon nanotubes (MWCNTs) and their derivates to environment have been studied. With γ-ray irradiation, MWCNTs were modified chemically with glucosamine and decylamine to obtain glucosamine-MWCNTs (g-MWCNTs) and decylamine-MWCNTs (d-MWCNTs). Their toxicological experiments were carried out with Tetrahymena pyriformis. The results illustrate that d-MWCNTs show a dose-dependent growth inhibition to the cells, due to the increasing concentration of toxic decylamine. This was attributed to the biological function performed by the decylamine after it was carried into the cell interior by the tubes. The results have a certain reference value for the applications of MWCNTs used as drug delivery system. Both glucosamine and purified MWCNTs (p-MWCNTs) alone show little biological activity, but g-MWCNTs exhibit a dose-dependent growth stimulation. This is due to the fact that the increasing hydrophilicity of g-MWCNTs promotes the conjugation of nanotubes with soluble peptone in culture medium via noncovalent binding. Uptake of the g-MWCNTs-peptone conjugates with various concentration of peptone by the cells is responsible for the dose-dependent growth stimulation. Consequently we propose the effects of concentration of functional groups, hydrophilicity of functionalized nanotubes as well as sequential nonspecific interaction between nanotubes with some components in culture medium on living system should be taken into account in the study of cytotoxicity of carbon nanotubes.
Keywords: tetrahymena pyriformi